The usage and management of credit card among UiTM Puncak Alam's staff / Fatin Hanani Azizan - Azizan, Fatin Hanani (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Nowadays, we can see that the usage of credit cards or 'plastic money' among Malaysians has become common, especially those people that always involved in trade. The surprising truth about credit card spending in Malaysia is as much as 8.21 Million numbers of credit cards in circulation in 2011 and there are 28.6 Million Malaysians. Thus, 1 in 3.48 Malaysians have a credit card in 2011. As an effort to profile credit card users in Malaysia, this paper seeks to explore preference of Malaysian bank customers to choose between Conventional and Islamic credit cards. The selection features are analyzed in terms of various factors, including the selection factors influenced by the credit cards‟ embedded features, the difference between the satisfaction and the loyalty level of Conventional Credit Card holders as compared to Islamic Credit Card holders and the customers‟ perceptions of Islamic Credit Card. The impact of credit cards is investigated through their usage as well as the perceptions of the credit card holders. In conducting the research, this study assembled primary data from staff in Universiti Teknologi MARA Selangor, Puncak Alam Campus through a questionnaire survey with 40 participants. The research indicates several determining factors for Malaysian revolving credit cardholders in terms of determining the impact of credit cards, namely, “education”, “income”, “credit behavior” and “number of credit cards held”